Respuesta :

Answer:

x = 2

y = -3

Step-by-step explanation:

Solve by substitution:

2x - y = 7

Move the 2x to the other side: -y = 7 - 2x

Divide by -1: y = -7 + 2x

Take the other equation: 3x + y = 3

Substitute y in: 3x + (-7 + 2x) = 3

Take out the parenthesis: 3x - 7 + 2x = 3

Move -7 to the other side: 3x + 2x = 3 + 7

Simplify: 5x = 10

x = 2

Take the first equation: 2x - y = 7

Substitute x back in: 2(2) - y = 7

Simplify: 4 - y = 7

-y = 3

y = -3

Answer:

1. x = 1/2y + 3.5

2. x = 1 - 1/3y

Step-by-step explanation:

1. add y on both sides then divide 2 by both sides. It will equal x = 1/2y + 3.5

2. subtract y from both sides then divide both sides by 3. You will get x = 1 - 1/3y.

ACCESS MORE